2018
DOI: 10.1515/ijamh-2017-0151
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming youth-friendly health services into existing primary health care facilities: experiences from South-South Nigeria

Abstract: Background Youth friendly services, an evidence based approach to overcome the barriers experienced by youths in accessing care, is poorly implemented. The Medical Women's Association of Nigeria (MWAN) Rivers State chapter, was supported by Ford Foundation to mainstream youth-friendly health services (YFHS) into existing primary health care facilities in two hard-to-reach communities. This paper presents the interventions, findings, challenges and recommendations. Methods This study project was implemented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…This is similar to a study conducted in 2018 by Ogu et al. [ 13 ]which revealed that the implementation of youth friendly health services remains minimal and are yet to be rolled out across all primary health centers in Nigeria.…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to a study conducted in 2018 by Ogu et al. [ 13 ]which revealed that the implementation of youth friendly health services remains minimal and are yet to be rolled out across all primary health centers in Nigeria.…”
Section: Discussionsupporting
confidence: 89%
“…Eight studies supported clinicians by employing peer navigators that work in tandem with youth-friendly clinic providers to support referral and linkage to the YFHSs, recruiting new clinic staff, and establishing new roles within the clinics (40,44,51,(54)(55)(56)(57)59). One study also implemented an adolescent HIV risk screening tool to help clinicians identify and prioritize high-risk patients (44).…”
Section: Support Cliniciansmentioning
confidence: 99%
“…(3) to deliver SRH services in ways that respond to the special needs of youths; (4) to appropriately provide STI diagnosis and treatment regimen for youths; and (5) to orient select youth to be advocates and change agents in their communities (i.e., peer educators). Ten studies reported the duration of the trainings and/or number of training sessions conducted, ranging from 1-5 days (38,(54)(55)(56)60)…”
Section: Train and Educate Stakeholdersmentioning
confidence: 99%
“…Implementing youth-friendly health services in schools and communities may assist in enabling reporting; the odds of youths utilizing health facilities increased when the services are youth friendly. 25 In this study, 76.2% of perpetrators were known or trusted by the survivor or the survivor's family. This finding is truly traumatic and impacts the willingness of survivors to report an incident.…”
Section: Discussionmentioning
confidence: 70%